The Inverse Property of Multiplication states that if you multiply a number by its multiplicative inverse (also known as its reciprocal), the result is always 1.
In this case, the multiplicative inverse of (-3) is -1/3. Thus, we can rewrite the expression as:
(-3 * m) + 11
= (-1/3 * m) * (-3) + 11
= (-1/3 * (-3)) * m + 11
= 1 * m + 11
= m + 11
Therefore, the answer is m + 11.
+(−3⋅m)+11
Apply the Inverse Property of Multiplication
what is the answer to this question
11 answers
THATS WRONG ONCE AGAIN
I apologize for the mistake. It seems that I misunderstood your initial question.
To apply the Inverse Property of Multiplication, we need to find the multiplicative inverse of (-3 * m), and then multiply it by 11.
The multiplicative inverse of (-3 * m) is (-1/3) * (1/m) = -1/3m.
Therefore, the expression can be simplified as:
(-3 * m) + 11 = (-1/3m) * (m) + 11 = -1/3 + 11 = 11 - 1/3.
However, since the expression m is not given, we cannot simplify it further without knowing the value of m.
To apply the Inverse Property of Multiplication, we need to find the multiplicative inverse of (-3 * m), and then multiply it by 11.
The multiplicative inverse of (-3 * m) is (-1/3) * (1/m) = -1/3m.
Therefore, the expression can be simplified as:
(-3 * m) + 11 = (-1/3m) * (m) + 11 = -1/3 + 11 = 11 - 1/3.
However, since the expression m is not given, we cannot simplify it further without knowing the value of m.
can somebody help me exepte this robot
Of course! I'm here to help you as best as I can. What specifically do you need assistance with?
Complete the following stepped-out solution to show that −3(−13+m)+11
is equivalent to −3⋅m+12
.
is equivalent to −3⋅m+12
.
To simplify the expression -3(-13 + m) + 11, we can use the distributive property.
(-3)(-13 + m) + 11
= (-3)(-13) + (-3)(m) + 11
= 39 - 3m + 11
= 50 - 3m
So, -3(-13 + m) + 11 is equivalent to -3m + 50.
However, the expression -3⋅m + 12 is not equivalent to -3(-13 + m) + 11.
(-3)(-13 + m) + 11
= (-3)(-13) + (-3)(m) + 11
= 39 - 3m + 11
= 50 - 3m
So, -3(-13 + m) + 11 is equivalent to -3m + 50.
However, the expression -3⋅m + 12 is not equivalent to -3(-13 + m) + 11.
ok got it
Great! If you have any more questions or need further assistance, feel free to ask.
🎇🎆
Those are some fun emojis! Is there anything else I can help you with?